2009
DOI: 10.1038/jp.2009.33
|View full text |Cite
|
Sign up to set email alerts
|

The utility of tracheal aspirate cultures in the immediate neonatal period

Abstract: Objective: Determine the contemporary incidence of pathogenic tracheal aspirate (TA) cultures when obtained within 12 h of birth, and to associate TA culture results with specific clinical conditions that increase the risk of infection.Study Design: A retrospective study over a 6-month period of admissions to a single outborn neonatal intensive care unit when a TA sample was collected within 12 h of birth (n ¼ 139).Result: In total, 9 of 139 (6.5%) TA cultures were positive for pathogenic bacterial growth. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…11 In neonates, the use of TAs to diagnose pneumonia may be useful when aspirates are collected in the immediate neonatal period, with an overall positive culture incidence of 6.5% in tracheal aspirate cultures obtained 12 hours after birth. 12 Interestingly, the Gram stain results in this study demonstrated low specificity and sensitivity for pathogen growth, consistent with our results, in which we found no statistical association with the number of WBCs on the Gram stain. 12 In contrast, in neonates who have been chronically intubated, the risk of colonization increases, therefore increasing the chances of obtaining a positive tracheal aspirate culture.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…11 In neonates, the use of TAs to diagnose pneumonia may be useful when aspirates are collected in the immediate neonatal period, with an overall positive culture incidence of 6.5% in tracheal aspirate cultures obtained 12 hours after birth. 12 Interestingly, the Gram stain results in this study demonstrated low specificity and sensitivity for pathogen growth, consistent with our results, in which we found no statistical association with the number of WBCs on the Gram stain. 12 In contrast, in neonates who have been chronically intubated, the risk of colonization increases, therefore increasing the chances of obtaining a positive tracheal aspirate culture.…”
Section: Discussionsupporting
confidence: 90%
“…12 Interestingly, the Gram stain results in this study demonstrated low specificity and sensitivity for pathogen growth, consistent with our results, in which we found no statistical association with the number of WBCs on the Gram stain. 12 In contrast, in neonates who have been chronically intubated, the risk of colonization increases, therefore increasing the chances of obtaining a positive tracheal aspirate culture. 13,14 One study in ventilated preterm infants using molecular identification of bacteria in tracheal aspirates found that in the first 72 hours after birth, most tracheal aspirate cultures had undetectable bacterial loads.…”
Section: Discussionsupporting
confidence: 90%
“… 126 The presence of white blood cells on tracheal aspirates has also been shown to have low specificity (54%) and sensitivity (67%) for VAP, even when there is bacterial growth on culture. 127 …”
Section: Necmentioning
confidence: 99%
“…1,4,5 The results from EACs are relatively nonspecific for infection and may be unreliable. [6][7][8][9][10][11][12][13][14][15][16] Sample collection and quality of specimens are variable, which may affect results. 16,17 Endotracheal secretion samples are from a nonsterile site, making the differentiation between colonization and infection in the culture challenging.…”
Section: Introductionmentioning
confidence: 99%